Analisis Dampak Sosial Pembangunan Kolam Retensi Andir terhadap Kehidupan Masyarakat Kelurahan Andir - Deanti Aulia Nasri; Mirna Nur Alia Abdullah; Cik Suabuana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Infrastructure development is something that is expected to change the socio-economic conditions of a community. The construction of Retention Ponds in the Andir Village area, Baleendah Subdistrict, Bandung Regency has the main function to overcome flooding problems that hamper the socio-economic activities of the community. The purpose of this research is to describe the social impact analysis of the Andir Retention Pond development on the condition of the Andir Village community. This research was conducted using a qualitative approach with a case study method. The data collection was carried out by means of observation, interviews, and documentation studies. The results showed that the construction of the Andir Retention Pond has had an impact on increasing the population, changing the urgency of infrastructure from flood control efforts to environmental management, sanitation, and economic support.